Development of Natural Fiber Hybrid Composites Using Sugarcane Bagasse and Bamboo Charcoal for Automotive Thermal Insulation Materials. (15th July 2021) - Abedom, Fasika; Sakthivel, S.; Asfaw, Daniel; Melese, Bahiru; Solomon, Eshetu; Kumar, S. Senthil
Abstract : The effective utilization of fibers from natural sources is the main objective of this research work, but natural fibers alone are not meeting the required strength properties. The objective of this study focuses on the experimental study of composites developed from bagasse fiber/bamboo charcoal for technical applications by investigating its diverse mechanical and thermal insulating properties. For this investigation, five hybrid composites with bagasse fiber/bamboo charcoal proportions of 100%/0%, 70%/30%, 50%/50%, 30%/70%, and 0%/100% with 65% polyurethane foam in all by using compression molding technique and their mechanical properties are evaluated experimentally under the ASTM standards. The fiber alignments, internal crack, and binding properties are checked by morphological test. It is observed that the tensile strength of sugarcane bagasse/charcoal composites produces 255.80 MPa which is approximately the same strength (260.10 MPa) as artificial fiber composites. The bagasse fiber/bamboo charcoal 30/70-based composites show a higher thermal insulation coefficient than the other four samples-reinforced composites. The impact and flexural strength of the 30/70 sample are higher than those of other samples. The results obtained report the possibility of exploitation of natural fiber sugarcane bagasse and bamboo charcoal for the production of reinforcements based on composites with good mechanical and thermal characteristics to utilize as automotive interior materials in component systems.